2007
DOI: 10.1016/j.buildenv.2006.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight concrete made from oil palm shell (OPS): Structural bond and durability properties

Abstract: The first part of this experimental program was to determine the structural bond properties of lightweight concrete incorporating solid waste oil palm shell (OPS) as coarse aggregate and also to compare its behaviour with other types of lightweight aggregate concretes. Other properties of OPS concrete namely the split tensile strength, modulus of rupture and modulus of elasticity were also determined. The structural bond properties were determined through pull-out test. The results showed that the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(99 citation statements)
references
References 14 publications
6
86
1
6
Order By: Relevance
“…This continual increase in strength even after 1 year indicates that the biomass mortar does not deteriorate once the OPKS aggregates are encapsulated into the mortar matrix. Similar trends were reported for OPKS as coarse aggregates in the literature [13]. Fig.…”
Section: Testing Proceduressupporting
confidence: 90%
“…This continual increase in strength even after 1 year indicates that the biomass mortar does not deteriorate once the OPKS aggregates are encapsulated into the mortar matrix. Similar trends were reported for OPKS as coarse aggregates in the literature [13]. Fig.…”
Section: Testing Proceduressupporting
confidence: 90%
“…The durability of OPS concrete has also been studied previously. When cured in water, it was found that OPS concrete have water absorption and water permeability of about 11% and 6.4 x 10 -10 cm/s respectively at an age of 28 day (Teo et al 2006), which is comparable to other lightweight concretes such as those made from pumice aggregates (Güdüz and Uğur 2005;Hossain 2004). …”
Section: Introductionmentioning
confidence: 70%
“…Therefore, such features and properties make OPS aggregates resistance to wear and due to its low impact and crushing values, it makes them absorbance to shock [17]. [14,15,[17][18][19][20].…”
Section: Oil Palm Shell (Ops)mentioning
confidence: 99%